Poly(d,l-lactide)/polyethylene glycol micro/nanofiber mats as paclitaxel-eluting carriers: preparation and characterization of fibers, in vitro drug release, antiangiogenic activity and tumor recurrence prevention - Hobzova, Radka; Hampejsova, Zuzana; Cerna, Tereza; Hrabeta, Jan; Venclikova, Kristyna; Jedelska, Jarmila; Bakowsky, Udo; Bosakova, Zuzana; Lhotka, Miloslav; Vaculin, Simon; Franek, Miloslav; Steinhart, Milos; et al. (Materials science & engineering. C, Materials for biological applications, 2019)
Poly(d,l-lactide)/polyethylene glycol (PLA/PEG) micro/nanofibers loaded with paclitaxel (PTX, 10 wt%) were prepared by needless electrospinning technology, which allows large scale production for real medicinal practice. The fiber structure and properties were investigated by several methods including scanning electron microscopy, nitrogen adsorption/desorption isotherm measurements, differential scanning calorimetry, and X-ray diffraction measurements to examine their morphology (fiber diameter distribution, specific surface area, and total pore volume), composition, drug-loading efficiency, and physical state. An HPLC-UV method was optimized and validated to quantify in vitro PTX release into PBS. The results showed that the addition of PEG into PLA fibers promoted the release of higher amounts of hydrophobic PTX over prolonged time periods compared to fibers without PEG. An in vitro cell assay demonstrated the biocompatibility of PLA/PEG fibrous materials and showed significant cytotoxicity of PTX-loaded PLA/PEG fibers against a human fibrosarcoma HT1080 cell line. The chick chorioallantoic membrane assay proved that PTX-loaded fibers exhibited antiangiogenic activity, with a pronounced effect in the case of the PEG-containing fibers. In vivo evaluation of PTX-loaded PLA/PEG fibers in a human fibrosarcoma recurrence model showed statistically significant inhibition in tumor incidence and growth after primary tumor resection compared to other treatment groups.
Keywords: buněčná smrt; nosiče léků; Antiangiogenesis; Drug Carriers; Angiogenesis Inhibitors; nádorové buněčné linie; paclitaxel; Local tumor recurrence; Needleless electrospinning; lidé; Paclitaxel quantification; X-Ray Diffraction; mužské pohlaví; Neoplasm Recurrence, Local; polyestery; Cell Line, Tumor; Polyethylene Glycols; lokální recidiva nádoru; kur domácí; polyethylenglykoly; Body Weight; Cell Death; Mice, Nude; Chickens; zvířata; Humans; nanovlákna; Temperature; Tumor Burden; PLA/PEG micro/nanofibers; tumor burden; tělesná hmotnost; myši nahé; Drug Liberation; viabilita buněk; uvolňování léčiv; Cell Survival; Polyesters; Nanofibers; inhibitory angiogeneze; Paclitaxel; CAM assay; difrakce rentgenového záření; teplota; Male; Animals